3. Malignant Testicular Neoplasia in Male Pig with Scrotal Hernia and Testicular Cyst: A Case Report - Gunanti Gunanti; Dwi Utari Rahmiati; Harits Abdullah Munir; Tytha Nadhifa Winarto; Septi Nurcholida Sari; Himah Nuradilah; Dina Zuhdina Rahman (Universitas Syiah Kuala, 2021)
A 4 month old male pig weighing 18.5 kg has enlarged testes. The mass in the scrotum is enlarge rapidly within 1 month, there is no known castration history of this animal. Pigs have a fairly good appetite, but have persistent diarrhea. Physical and supporting examinations (radiography, ultrasonography, hematology and blood chemistry) were performed. Radiographic results showed radiopaque nodules in the lungs, gas distension in the fundus and intestines that were imaged radiolucently, and radiopaque masses in the testis-scrotum. Based on the results of ultrasonography, it is known that the bladder is surrounded by intestinal organs and some anechoic areas are seen on the sonogram of the testes. Hematological and blood chemistry data obtained showed that the animals had hypochromic anemia, decreased ALP values, and had leukocytosis. The results of the investigations carried out were not clear enough to determine the cause of the enlargement of the pig's testicles, so a surgical approach was carried out with a dubius-infausta prognosis. The results of this approach were adjusted with the results of the previous investigations and concluded that the pigs had malignant testicular neoplasia, scrotal hernia, and testicular cyst.